The impact of COVID-19 pandemic on food habits and neophobia in children in the framework of the family context and parents’ behaviors: A study in an Italian central region - Di Nucci, Annalisa; Scognamiglio, Umberto; Grant, Federica; Rossi, Laura (Frontiers in Nutrition, 2022)
This paper aims to evaluate the impact of Covid-19 social restrictions on eating habits and food neophobia in children living in an Italian central region. In a sample of 99 children, 97% showed no worsening of neophobia meaning that the selective food refusal did not change in the pandemic period. About 70% of participants did not change their eating habits, with some subgroups reporting an increase in the consumption of fruits (22.2%), vegetables (19.2%), and legumes (21.2%). Relevantly the impact of the pandemic on the sedentary attitude passed from 25.3% to 70.7%. Neophobia was not associated with ponderal status. However, in normal-weight children a high prevalence of intermediate level neophobia (78.4%) was found. 39.4% of the studied children were involved in meal preparation during social isolation, with an increase in the proportion of children that shared all meals with their family (32.3% versus 78.8%). Non-coercive parent behaviors in reaction to food refusal was associated with low levels of neophobia. In this sample, the pandemic positively affected children's food habits and neophobia through the mediation of parents’ attitudes. The main implication of the study is the importance of capitalizing on the period of restrictions in order to involve children in meal sharing and food preparation.